Albumin Levels in Tear Film Modulate the Bioavailability of Medically-Relevant Topical Drugs - Sebbag, Lionel; Moody, Leah M.; Mochel, Jonathan P. (Frontiers in Pharmacology, 2020)
The breakdown of blood-tear barrier that occurs with ocular pathology allows for large amounts of albumin to leak into the tear fluid. This process likely represents an important restriction to drug absorption in ophthalmology, as only the unbound drug is transported across the ocular tissue barriers to exert its pharmacologic effect. We aimed to investigate the effects of albumin levels in tears on the bioavailability of two commonly used ophthalmic drugs: tropicamide, an antimuscarinic that produces mydriasis and cycloplegia, and latanoprost, a PGF2α analog used for the treatment of glaucoma. Eight female beagle dogs underwent a randomized, vehicle-controlled crossover trial. For each dog, one eye received 30 µL of artificial tears (control) or canine albumin (0.4 or 1.5%) at random, immediately followed by 30 µL of 1% tropicamide (2 days, 24h washout) or 0.005% latanoprost (2 days, 72h washout) in both eyes. Pupil diameter (digital caliper) and intraocular pressure (IOP; rebound tonometry) were recorded at various times following drug administration (0 to 480 min) and compared between both groups with a mixed model for repeated measures. Albumin in tears had a significant impact on pupillary diameter for both tropicamide (P≤0.001) and latanoprost (P≤0.047), with no differences noted between 0.4% and 1.5% concentrations. Reduction in the maximal effect (pupil size) and overall drug exposure (area under the effect time-curve of pupil size over time) were significant for tropicamide (6.2-8.5% on average, P≤0.006) but not for latanoprost (P≥0.663). The IOP, only measured in eyes receiving latanoprost, was not significantly impacted by the addition of either 0.4% (P = 0.242) or 1.5% albumin (P = 0.879). Albumin in tear film, previously shown to leak from the conjunctival vasculature in diseased eyes, may bind to topically administered drugs and reduces their intraocular penetration and bioavailability. Further investigations in clinical patients and other commonly used ophthalmic medications are warranted.